Rekonstruksi Asbabun Nuzul Sebagai Metodologi Interpretasi Teks Al-Qur’an - Wely Dozan (Al Hikmah: Jurnal Studi Keislaman, 2020)
Abstract, the study of Asbabun Nuzul as seen by some scholars is very important to be used in interpreting the texts of the Qur'an. Mufassir scholars never separated from a historical text of the Koran. However, the use of the asbabun nuzul qur'an theory of classical clerics often only looks at the context of the fall of the verse so that among some contemporary thought try to reconstruct the asbabun nuzul qur'an theory in this present era. Specifically, interpreting the text of the Qur'an through its history by looking at several structures namely, First, Seeing asbabun nuzul qur'an macro. Second, see the asbabun nuzul qur‟an micron in determining the true values of the Qur'an. The approach used in this paper is the literature study approach to find various concepts of Asbabun Nuuz theory through books, journals, and so on. The conclusion is that the asbabun nuzul al-Qur'an theory basically does not only refer to the historical context of the fall of verses in earlier times, but is contextualized with the relation between macro and micro to find meaning and values in the substance of the text of the verse. Keywords: Theory, Asbabun Nuzul, al-Qur'an